Dihydropyrimidinone-isatin hybrids as novel non-nucleoside HIV-1 reverse transcriptase inhibitors - Devale, T. L.; Parikh, J.; Miniyar, P.; Sharma, P.; Shrivastava, B.; Murumkar, P. (Bioorganic Chemistry, 2017)
A novel series of substituted N-(2-( 2,3-dioxoindolin-1-yl) acetyl)-2-oxo-1,2,3,4-tetrahydropyrimidine-5carboxamide was designed, synthesized and evaluated for in vitro Reverse Transcriptase (RT) inhibitory activity. This series is a combination of peculiar structural features from leading scaffolds of [(2-hydroxye thoxy) methyl]-6-(phenylthio) thymine (HEPT) and oxyindole. In vitro screening led to identification of two hybrids (9c and 9d) possessing higher RT inhibitory activity than the standard rilpivirine. Docking study was performed to study the binding orientations of synthesized hybrids towards RT enzyme.